Transitional Arrangements for Trade and Payments Among the CMEA Countries. (IMF Working Papers; Working Paper ;, 1990)
Trade among the CMEA countries will soon be conducted at world prices and in convertible currencies. These are crucial steps in economic reform but will worsen Eastern Europe's terms of trade and drive it into current account deficit with the USSR. Proposals have been made for a payments union, resembling the European Payments Union of 1950-1958, to ease the transition. But it would not be very helpful if confined to the countries of Eastern Europe and would not function well if it included the USSR, which would be a persistent creditor. Other ways must be found to deal with the transition.